Anaceting Mobile Health Application: An Innovative Digital Solution for Early Stunting Detection in Indonesian Children - Riski Novera Yenita; Viana Anggraini; Afdhal Islami; Khaidir Ansyari (Postgraduate, University of Mataram, 2025)
Stunting is a complicated public health problem in Indonesia, with a countrywide rate of 21.5% in 2023. Puskesmas Rejosari in Pekanbaru City had the most stunting instances, with 50 out of 239. This shows that new ways are needed to find stunting cases early and teach people in the community about it. The goal of this study is to create the ANACETING (Stunting Prevention Information Application) Android app as a digital tool for finding stunting in toddlers early. The study is at the fourth stage of the Research and Development (R&D) approach and includes 30 mothers of toddlers as test subjects.A panel of media and material experts conducted validation using a structured questionnaire with 22 items on a Likert scale instrument. The app contains tools for measuring growth, interactive educational content, guidelines for supplementary feeding, immunization schedules, and a space for individuals in the community to chat about topics. The media expert gave it a score of 4.00 (in the